IVR design and review of advanced NPPs in China: Issues and perspectives - Yang Zhiyi; Zhang Ningna; Zhu Dahuan; Ding Chao; Song Mingqiang; Xiao Hong (International Journal of Advanced Nuclear Reactor Design and Technology, 2021)
The In-Vessel Retention (IVR) is an attractive strategy which could avoid the failure of Reactor Pressure Vessel (RPV) and consequent phenomenon in severe accident of nuclear power plants (NPPs). Most advanced NPPs designed in China adopt the IVR measure, e.g. ACPR1000, CAP1400 and HPR1000. In this paper, the IVR designs of different advanced NPPs in China are described and compared, and relevant IVR analyses and experimental work are introduced, then several key IVR technical issues are discussed and corresponding technical positions are given. In general, IVR is proposed as an effective measure based on current analysis, also several suggestions are put forward to further improve the likelihood of IVR success.